Dynamic Duopoly with Differentiated Goods and Sluggish Demand - Mononen, Mikko (My University, 2022)
This thesis investigates dynamic Bertrand competition between two firms in a market where the goods are differentiated and demand is sluggish. Unlike homogeneous goods, differentiated goods are not perfect substitutes for each other. Sluggish demand means that there is a delay in the adjustment of demand after price changes. Sluggish demand is a remarkably ignored topic in the economic literature. The competitive situation is modelled as a differential game. The dynamic model employs the demand system as in Singh and Vives 1984 and dynamics as in Wirl 2010. It is shown that the dynamic model has a unique symmetric open-loop Nash equilibrium. The long-term open-loop steady state is compared with the equilibrium point of the static model. The fundamental mathematical theory and solution methods of optimal control theory and differential games that are required in the analysis of the model are also presented in the thesis. As the main result of the analysis of the model, it is shown that when sluggishness of demand is relatively small (i.e. the adjustment of demand after price changes is sufficiently fast), sluggishness of demand increases the market power and profits of the firms in the open-loop steady state compared to the equilibrium point of the static model. After sluggishness of demand exceeds a certain point, the profits of the firms decline below the static equilibrium profits. Moreover, it is shown that product differentiation relaxes price competition also in the presence of sluggish demand, as it does in a static model.

Tutkielmassa tarkastellaan kahden yrityksen välistä dynaamista Bertrand-kilpailua markkinoilla, joilla hyödykkeet ovat differoituja ja kysyntä on jäykkää. Toisin kuin homogeeniset hyödykkeet, differoidut hyödykkeet eivät ole täydellisiä korvikkeita toisilleen. Kysynnän jäykkyys tarkoittaa sitä, että kysyntä sopeutuu viiveellä hinnanmuutoksiin. Kysynnän jäykkyys on yllättävän vähälle huomiolle jäänyt aihe taloustieteellisessä kirjallisuudessa. Kilpailutilanne mallinnetaan differentiaalisena pelinä. Dynaamisen mallin kysyntäjärjestelmä on kuten Singh ja Vivesin (1984) ja dynamiikka kuten Wirlin (2010) artikkelissa. Dynaamisella mallilla osoitetaan olevan uniikki symmetrinen open-loop Nash -tasapainostrategia. Pitkän aikavälin open-loop -tasapainopistettä vertaillaan staattisen Bertrand-mallin tasapainopisteen kanssa. Tutkielmassa esitetään lisäksi mallin tarkasteluun vaadittavan optimaalisen kontrolliteorian ja differentiaalisten pelien keskeinen matemaattinen teoria ja ratkaisumenetelmät. Mallin analyysin päätuloksena osoitetaan, että kun kysynnän jäykkyys on verrattain pientä (ts. kysynnän sopeutuminen hinnanmuutoksiin on riittävän nopeaa), kysynnän jäykkyys lisää yritysten markkinavoimaa ja voittoja open-loop -tasapainopisteessä verrattuna staattiseen tasapainopisteeseen. Kun kysynnän jäykkyys ylittää tietyn pisteen, yritysten voitot laskevat staattisten tasapainovoittojen alle. Lisäksi osoitetaan, että tuotedifferointi pehmentää hintakilpailua myös kysynnän jäykkyyden olosuhteissa, aivan kuten staattisessa mallissa.
Keywords: Industrial organisation, game theory, differential games, oligopoly, price competition, sluggish demand, dynamical systems